Welcome to Scribd. Sign in or start your free trial to enjoy unlimited e-books, audiobooks & documents.Find out more
Standard view
Full view
of .
0 of .
Results for:
P. 1
Derivatives & Integrals Formulas

# Derivatives & Integrals Formulas

Ratings: (0)|Views: 86|Likes:
This document provides formulas to solve proplems related to derivatives and integrals.
This document provides formulas to solve proplems related to derivatives and integrals.

### Availability:

See more
See less

04/02/2013

pdf

text

original

Derivative Formulas
General Rules
dx
[
(
x
)
+
g
(
x
)]
=
(
x
)
+
g
(
x
)
dx
[
(
x
)
g
(
x
)]
=
(
x
)
g
(
x
)
dx
[
c
(
x
)]
=
c
(
x
)
dx
[
(
g
(
x
))]
=
(
g
(
x
))
g
(
x
)
dx
[
(
x
)
g
(
x
)]
=
(
x
)
g
(
x
)
+
(
x
)
g
(
x
)
dx
(
x
)
g
(
x
)
=
f
(
x
)
g
(
x
)
(
x
)
g
(
x
)[
g
(
x
)]
2
Power Rules
dx
(
x
n
)
=
nx
n
1
dx
(
c
)
=
0
dx
(
cx
)
=
cdx
(
√
x
)
=
12
√
x
Exponential
dx
[
e
x
]
=
e
x
dx
[
a
x
]
=
a
x
ln
e
u
(
x
)
=
e
u
(
x
)
u
(
x
)
dx
e
rx
=
r e
rx
Trigonometric
dx
(sin
x
)
=
cos
xdx
(cos
x
)
=
sin
xdx
(tan
x
)
=
sec
2
xdx
(cot
x
)
=
csc
2
xdx
(sec
x
)
=
sec
x
tan
xdx
(csc
x
)
=
csc
x
cot
x
Inverse Trigonometric
dx
(sin
1
x
)
=
1
√
1
x
2
dx
(cos
1
x
)
=
1
√
1
x
2
dx
(tan
1
x
)
=
11
+
x
2
dx
(cot
1
x
)
=
11
+
x
2
dx
(sec
1
x
)
=
1
|
x
|√
x
2
1
dx
(csc
1
x
)
=
1
|
x
|√
x
2
1
Hyperbolic
dx
(sinh
x
)
=
cosh
xdx
(cosh
x
)
=
sinh
xdx
(tanh
x
)
=
sech
2
xdx
(coth
x
)
=
csch
2
xdx
(sech
x
)
=
sech
x
tanh
xdx
(csch
x
)
=
csch
x
coth
x
Inverse Hyperbolic
dx
(sinh
1
x
)
=
1
√
1
+
x
2
dx
(cosh
1
x
)
=
1
√
x
2
1
dx
(tanh
1
x
)
=
11
x
2
dx
(coth
1
x
)
=
11
x
2
dx
(sech
1
x
)
=
1
x
√
1
x
2
dx
(csch
1
x
)
=
1
|
x
|√
x
2
+
1

Table of Integrals
Forms Involving
a
+
bu
1.

1
a
+
budu
=
1
b
ln
|
a
+
bu
|+
c
2.

ua
+
budu
=
1
b
2
(
a
+
bu
a
ln
|
a
+
bu
|
)
+
c
3.

u
2
a
+
budu
=
12
b
3
[(
a
+
bu
)
2
4
a
(
a
+
bu
)
+
2
a
2
ln
|
a
+
bu
|
]
+
c
4.

1
u
(
a
+
bu
)
du
=
1
a
ln
ua
+
bu
+
c
5.

1
u
2
(
a
+
bu
)
du
=
ba
2
ln
a
+
buu
1
au
+
c
Forms Involving (
a
+
bu
)
2
6.

1(
a
+
bu
)
2
du
=
1
b
(
a
+
bu
)
+
c
7.

u
(
a
+
bu
)
2
du
=
1
b
2
aa
+
bu
+
ln
|
a
+
bu
|
+
c
8.

u
2
(
a
+
bu
)
2
du
=
1
b
3
a
+
bu
a
2
a
+
bu
2
a
ln
|
a
+
bu
|
+
c
9.

1
u
(
a
+
bu
)
2
du
=
1
a
(
a
+
bu
)
+
1
a
2
ln
ua
+
bu
+
c
10.

1
u
2
(
a
+
bu
)
2
du
=
2
ba
3
ln
a
+
buu
a
+
2
bua
2
u
(
a
+
bu
)
+
c
Forms Involving
a
+
bu
11.

u
√
a
+
bu du
=
215
b
2
(3
bu
2
a
)(
a
+
bu
)
3
/
2
+
c
12.

u
2
√
a
+
bu du
=
2105
b
3
(15
b
2
u
2
12
abu
+
8
a
2
)(
a
+
bu
)
3
/
2
+
c
13.

u
n
√
a
+
bu du
=
2
b
(2
n
+
3)
u
n
(
a
+
bu
)
3
/
2
2
nab
(2
n
+
3)

u
n
1
√
a
+
bu du
14.

√
a
+
buudu
=
2
√
a
+
bu
+
a

1
u
√
a
+
budu
15.

√
a
+
buu
n
du
=
1
a
(
n
1)(
a
+
bu
)
3
/
2
u
n
1
(2
n
5)
b
2
a
(
n
1)

√
a
+
buu
n
1
du
,
n
=
1

16a.

1
u
√
a
+
budu
=
1
√
a
ln
√
a
+
bu
√
a
√
a
+
bu
+√
a
+
c
,
a
>
0
16b.

1
u
√
a
+
budu
=
2
√
a
tan
1
a
+
bu
a
+
c
,
a
<
0
17.

1
u
n
√
a
+
budu
=
1
a
(
n
1)
√
a
+
buu
n
1
(2
n
3)
b
2
a
(
n
1)

1
u
n
1
√
a
+
budu
,
n
=
1
18.

u
√
a
+
budu
=
23
b
2
(
bu
2
a
)
√
a
+
bu
+
c
19.

u
2
√
a
+
budu
=
215
b
3
(3
b
2
u
2
4
abu
+
8
a
2
)
√
a
+
bu
+
c
20.

u
n
√
a
+
budu
=
2(2
n
+
1)
bu
n
√
a
+
bu
2
na
(2
n
+
1)
b

u
n
1
√
a
+
budu
Forms Involving
a
2
+
u
2
,
a
>
0
21.

a
2
+
u
2
du
=
12
u
√
a
2
+
u
2
+
12
a
2
ln
u
+√
a
2
+
u
2
+
c
22.

u
2
a
2
+
u
2
du
=
18
u
(
a
2
+
2
u
2
)
√
a
2
+
u
2
18
a
4
ln
u
+√
a
2
+
u
2
+
c
23.

√
a
2
+
u
2
udu
=
a
2
+
u
2
a
ln
a
+√
a
2
+
u
2
u
+
c
24.

√
a
2
+
u
2
u
2
du
=
ln
u
+
a
2
+
u
2
√
a
2
+
u
2
u
+
c
25.

1
√
a
2
+
u
2
du
=
ln
u
+
a
2
+
u
2
+
c
26.

u
2
√
a
2
+
u
2
du
=
12
u
a
2
+
u
2
12
a
2
ln
u
+
a
2
+
u
2
+
c
27.

1
u
√
a
2
+
u
2
du
=
1
a
ln
ua
+√
a
2
+
u
2
+
c
28.

1
u
2
√
a
2
+
u
2
du
=√
a
2
+
u
2
a
2
u
+
c
Forms Involving
a
2
¯¯
u
2
,
a
>
0
29.

a
2
u
2
du
=
12
u
√
a
2
u
2
+
12
a
2
sin
1
ua
+
c
30.

u
2
a
2
u
2
du
=
18
u
(2
u
2
a
2
)
√
a
2
u
2
+
18
a
4
sin
1
ua
+
c
31.

√
a
2
u
2
udu
=
a
2
u
2
a
ln
a
+√
a
2
u
2
u
+
c
32.

√
a
2
u
2
u
2
du
=√
a
2
u
2
u
sin
1
ua
+
c